Avaliação de torques de inserção e de remoção e alterações de superfície de implantes porous e porous nano - Negrão , Luciane Ferreira (2014)
The present study aimed to evaluate microscopically the surface of dental implants, Porous and Porous Nano, when subjected to different torques after 40 days of implantation in rabbit tibia, as well as incidence of cracks and fractures when different torques applied in vitro in implants Conexão - Master Actives and Easy Grip Porours and Active. Six healthy New Zealand male adult rabbits received two types of implants, Porous (treated with acids) and Porous Nano (treated with acid followed by soaking in solution with fluoride) in the left tibia. The implants were installed and removed with different torques. The animals were sacrificed at 40 days. The implants were removed and their surfaces examined by scanning electron microscopy, obtained to measure the proportion of surface covered by adhering bone tissue. The right tibia of animals was used for installation of implants in vitro with different implant insertion and removal torques and different milling technias, with these tibias were photographed in Biological Monocular Microscope for measuring the length of the lines of cracks/fractures. Therefore, it was concluded that there is no significant differences in the insertion/removal torques between Porous and Porous Nano implants. However, there is a trend to a higher adherence of bone tissue to the surface of Porous implant when compared to Porous Nano. The in vitro production of fractures and cracks in rabbit tibia can be associated to the type of milling, in addition to the applied removal/insertion torques. Moreover, the removal torque seems to be lower than the insertion torque, regardless of the implant surface.